Supply Chain Policy for the Worldview of Innovations - Ridzuan Masri; Wan Mohd Azfar Wan Mohd Zain; Normy Rafida Abdul Rahman; Muhammad Zeeshan (International Journal of Supply Chain Management, 2019)
Abstract— Innovation is an important activity to ensure the organization's sustainability which strongly depends on the supply chain policy of the system. In addition to generating profits to the organization, innovation should also be an act that can warrant well-being not only to the present generation's life, but to future generations as well and for Islam, including well-being in the hereafter. This means, innovation is not just an ordinary activity, but a responsibility to be implemented. Nevertheless, the approach of innovation between the west and Islam is different. Before an innovation could take place, it is important and worthy for an innovator to comprehend the worldview of both civilizations as there are ethical boundaries that separate the objectives, ways, and direction of an innovation. This article discusses perspective of innovation from both Islamic and western worldview and its relationship with innovation in narrative methodology.